A design and simulation of the opportunistic computation offloading with learning-based prediction for unmanned aerial vehicle (UAV) clustering networks - Valentino, Rico; Jung, Woo Sung; Ko, Young Bae (Sensors (Switzerland), 2018)
Drones have recently become extremely popular, especially in military and civilian applications. Examples of drone utilization include reconnaissance, surveillance, and packet delivery. As time has passed, drones’ tasks have become larger and more complex. As a result, swarms or clusters of drones are preferred, because they offer more coverage, flexibility, and reliability. However, drone systems have limited computing power and energy resources, which means that sometimes it is difficult for drones to finish their tasks on schedule. A solution to this is required so that drone clusters can complete their work faster. One possible solution is an offloading scheme between drone clusters. In this study, we propose an opportunistic computational offloading system, which allows for a drone cluster with a high intensity task to borrow computing resources opportunistically from other nearby drone clusters. We design an artificial neural network-based response time prediction module for deciding whether it is faster to finish tasks by offloading them to other drone clusters. The offloading scheme is conducted only if the predicted offloading response time is smaller than the local computing time. Through simulation results, we show that our proposed scheme can decrease the response time of drone clusters through an opportunistic offloading process.
Keywords: Clustering networks; Computation offloading; Computational Offloading; Computing resource; Design and simulation; High intensity; Packet Delivery; Wireless communications; Computation offloading; Drone cluster; Neural network; Wireless communication